Near-term climate impacts of Finnish residential wood combustion - Savolahti, Mikko; Karvosenoja, Niko; Soimakallio, Sampo; Kupiainen, Kaarle; Tissari, Jarkko; Paunu, Ville-Veikko (Energy Policy, 2022)
Residential wood combustion (RWC) is a major source of climate-impacting emissions, like short-lived climate forcers (SLCF) and biogenic CO2, in Finland. In this paper, we present projections for those emissions from 2015 to 2040. We calculated the climate impact of the emissions using regional temperature potential metrics presented in literature. In our results, the climate impacts are given as global and Arctic temperature responses caused by the studied emissions in a 25 year time span. The results show that SLCF emissions from RWC cause a significant warming impact. Using our selected metrics, SLCF emissions from RWC added to the warming impact of Finland's projected greenhouse gas emissions by 28% in global temperature response and by 170% in Arctic response. When compared with other common heating methods in Finnish detached houses, using a typical Finnish stove (masonry heater) was the least climate-friendly option. Taking biogenic CO2 emissions into account further highlighted this finding. Finally, we assessed the change in climate impact when implementing various emission reduction measures for RWC. With a time span of 25 years, early action was found to be even more crucial than the eventual reductions in annual emissions in 2040. Highlights • RWC is the major source of BC and many other SLCFs in Finland. • SLCF emissions from Finnish RWC have a relatively significant climate impact, compared with GHGs. • Using a stove was found to be the least climate-friendly option to heat a house. • Biogenic CO2 emissions need to be included in assessments. • Early action is key in SLCF emission reduction measures.